Міжнародний туризм в Україні: геополітичні аспекти глобального явища - Парфіненко, А.Ю. (Київський національний університет імені Тараса Шевчена, 2015)
Стаття присвячена дослідженню функціональних можливостей міжнародного туризму виступати каналом «публічної дипломатії». Визначено основні чинники, які в умовах глобалізації перетворюють світові туристичні потоки на інструмент зов- нішньополітичного впливу. Охарактеризовано динаміку міжнародних туристичних прибуттів в другій половини XX – на початку XXI ст., які представлені як глобальний простір соціальних мереж та відповідних економічних і геополітичних впливів. Висвітлено основні підходи «нової публічної дипломатії» у межах якої соціальні інститути та процеси (у тому числі, туризм) розглядаються як самостійні суб’єкти міжнародних відносин та важливі складові «м’якої сили». Розкрито конструктивну роль туризму в формуванні глобального рейтингу «м’якої сили» та рейтингу національний брендів. Стверджується про наявність прямої кореляції між туристичною привабливістю та можливістю здійснення «м’якого» впливу. Обґрунтовано доцільність посилення промоції національного туристичного продукту як дієвого інструменту публічної дипломатії в Україні. Робиться висновок, що в умовах глобалізації туризм набуває політичної ваги як чинник неформальних міжнародних контактів, додаткового інструменту досягнення зовнішньополітичних інтересів держави і базової основи публічної дипломатії, а сама дипломатія може виступати дієвою стратегією розвитку національного туризму.
INTERNATIONAL TOURISM AS A TOOL OF PUBLIC DIPLOMACY: NEW OPPORTUNITIES OF STRENGTHENING FOREIGN INFLUENCE OF UKRAINE Parfinenko A. Y. Ph.D in history, dozent, V. N. Karazin Kharkiv National University, Head of the Department of Tourism Business. Abstract. The article examines functional capabilities of international tourism to perform as a channel of «public diplomacy». The author defines the main factors, which in the terms of globalization, transform the world tourist flows into a foreign policy tool of influence. The article characterizes the dynamics of international tourist arrivals in the second half of the XX - early XXI century, which are represented as a global space of social networks and corresponding economic and geopolitical influences. The paper highlights basic approaches of «new public diplomacy» within which social institutions and processes (including tourism) are considered as independent subjects of international relations and important components of «soft power». The study reveals constructive role of tourism in shaping the global rating of «soft power» and the rating of national brands. It is claimed that there’s a direct correlation between tourist attraction and an opportunity to exert «soft» influence. The article grounds expediency of strengthening the promotion of national tourist product as an effective tool of public diplomacy in Ukraine. The author comes to the conclusion that in the terms of globalization tourism is gaining political weight as a factor in informal international contacts, additional tool to achieve foreign policy interests of the state and basic foundation of public diplomacy and diplomacy can be represented as an operational strategy for the development of national tourism. Key words: public diplomacy, cultural diplomacy, soft power, international tourism, tourist flows, tourist image, national brand.
Keywords: Research Subject Categories::SOCIAL SCIENCES; публічна дипломатія; культурна дипломатія; м’яка сила; міжнародний туризм; туристичні потоки; туристичний імідж; національний бренд